PROFIL DISTRIBUSI DAN KONDISI MANGROVE BERDASARKAN PASANG SURUT AIR LAUT DI PULAU BANGKOBANGKOANG KECAMATAN LIUKANG TUPABBIRING KABUPATEN PANGKEP - Hayati, Nurul Fitri; Muhiddin, Amir Hamzah; Amran, Muhammad Anshar (Jurnal Ilmu Kelautan SPERMONDE, 2017)
Mangrove forests are a community of tropical and subtropical beach vegetation, capable of growing and developing in tidalareas. This study aims to obtain information on the type and density of mangrove species by using remote sensing applicationsand to obtain mangrove distribution profile based on tidal. This research has been conducted in Bangkobangkoang IslandTupabbiring Sub-district of Pangkep Regency in September-October 2016. This research covers species inventory, mangrovedensity level using Landsat 8 image with Acquisition 6 June 2016 and mangrove distribution based on sea tides. The resultsshowed that mangrove vegetation density conditions in Bangkobangkoang island were generally in good condition. The typesof mangroves on the island of Bangkobangkoang are Rhizophora stylosa, Rhizophora apiculata, Rhizophora mucronata,Sonneratia alba, and Avicennia marina. The dominant mangrove species are Rhysophora stylosa and Rhizophora apiculata.Mangrove distributed at the highest tide with Rhyzophora stylosa type will be submerged while at lowest tide generally nomangrove is submerged except on the western island with the same type of Rhyzophora stylosaKey words: Mangrove, Landsat-8, Density, Ddistributions profile